Legal Analysis Of The Validity Of Electronic Documents And Signatures As Evidence In Legal Proceedings In Indonesia - Roslaili (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze the validity and evidentiary value of electronic documents and signatures in legal proceedings in Indonesia following the enactment of Law No. 1 of 2024 on Electronic Information and Transactions. This study uses a normative legal research method with a legislative and conceptual approach. The research population consists of legal norms and legal doctrines related to electronic evidence, while the research sample includes Law Number 1 of 2024, Government Regulation Number 71 of 2019, HIR, RBg, as well as relevant court decisions and scientific literature. The research instrument is a literature study of primary and secondary legal materials analyzed qualitatively using deductive reasoning. The results show that electronic documents and signatures are normatively recognized as valid evidence. However, in judicial practice, their evidentiary value is still relative because they are generally positioned as private deeds and are highly dependent on the judge's assessment. This study concludes that although regulations have provided a strong legal basis, strengthening technical regulations and increasing the understanding of law enforcement officials is still necessary to ensure legal certainty in electronic evidence.